Applications of optically and electrically driven nanoscale bowtie antennas - Zhongjun Jiang; Yingjian Liu; Liang Wang (Opto-Electronic Science, 2022)
Optical antennas play an important role in optical field manipulation. Among them, nanoscale bowtie antennas have been extensively studied for its high confinement and enhancement. In this mini-review, we start with a brief introduction of bowtie antennas and underlying physics. Then we review the applications with respect to optically and electrically excited nanoscale bowtie antennas. Optically driven bowtie antennas enable a set of optical applications such as near-field imaging/trapping, nonlinear response, nanolithography, photon generation and detection. Finally, we put emphasis on the principle and applications of electrically driven bowtie antennas, an emerging method of generating ultrafast and broadband tunable nanosources. In a word, nanoscale bowtie antennas still have great potential research value to explore.